Intestinal dysbiosis during pregnancy and microbiota-associated impairments in offspring - Abu, Yaa; Roy, Sabita (Frontiers in Microbiomes, 2025)
The maternal microbiome is increasingly being recognized as a key determinant in various neonatal health outcomes, including offspring immunity, metabolism, brain function, and behavior. While the oral, vaginal, skin, and gut microbiota are significant contributors to the offspring’s postnatal gut microbial seeding, the composition and diversity of the maternal gut microbiome during pregnancy seems to be critical in shaping neonatal health outcomes, even prior to birth. Growing evidence suggests that the balance among the microbial groups in the gut and their interactions with the host are crucial for health. Dysbiotic communities in pregnancy and early in life may lead to disease processes in offspring, though the specific processes by which maternal gut microbes affect offspring gut microbial development are unknown. Here, we summarize research examining gut microbial shifts during pregnancy, and their effects on the diversity and composition of the infant microbiome and on early health outcomes. We also discuss current theories for how the maternal gastrointestinal (GI) tract influences neonatal seeding, and how probiotics during the perinatal period may affect offspring health outcomes.